Analisis Manfaat Ekonomi, Ekologi, dan Sosial pada Integrasi Padi-Itik (Studi Kasus Pertanian Terpadu Pakkampi Kabupaten Sidenreng Rappang) - Hidayah, Nurul; Ambar, Abdul Azis (Universitas Galuh, 2025)
Sustainable farming systems are a solution to overcome the challenges of conventional rice cultivation which still relies on chemicals and has high production costs. One sustainable approach is rice-duck integration, which combines rice cultivation with duck rearing to increase productivity and efficiency of farming businesses. This research aims to analyze the economic, ecological and social benefits of the rice-duck integration system in Pakkampi Farming Enterprises, Panca Rijang District, Sidenreng Rappang Regency. This research uses a quantitative descriptive method with purposive sampling technique. Data was collected through interviews and secondary data analysis from the local Agriculture Service. Data analysis was carried out descriptively. For the economic aspect, descriptive analysis is used to calculate business efficiency using the R/C ratio (Revenue to Cost Ratio). Meanwhile, the ecological aspect uses quantitative soil testing using a soil testing device (PUTS) and the social aspect is analyzed using quantitative descriptive methods. The research results show that the rice-duck integration system provides significant economic benefits with an R/C ratio of 5.7, indicating that this business is very profitable. From an ecological aspect, this system reduces the use of chemical pesticides through natural pest control by ducks and increases soil fertility with duck droppings as organic fertilizer. Socially, this integration strengthens cooperation between farmers, improves farmer welfare, and provides healthier food products. Thus, the rice-duck integration system has proven to be a sustainable, efficient and effective agricultural model for local farmers.